2021
DOI: 10.3390/app11104568
|View full text |Cite
|
Sign up to set email alerts
|

Slope Stability Analysis to Correlate Shear Strength with Slope Angle and Shear Stress by Considering Saturated and Unsaturated Seismic Conditions

Abstract: Assessment and analysis of soil slope stability is an important part of geotechnical engineering at all times. This paper examines the assessment of soil slope stability in fine-grained soils. The effect of change in shear strength (τ), shear stress (σ) and slope angle (β) on the factor of safety has been studied. It correlates shear strength with slope angle and shear stress by considering the horizontal seismic coefficients in both saturated and unsaturated conditions. The slope failure surface was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Over time, the literature has been enriched with numerous methods for stability analyses, developed by academics and researchers in the field, among which we mention: methods based on the limit equilibrium concept [1][2][3][4][5][7][8][9][10]; methods based on finite element/difference method [3,4,[7][8][9][10]12,13,49] (which is a modern and accurate one, able to be applied to complex structures); methods based on 3D analyses [29,40,41,[50][51][52][53][54] (for slopes with complex geometries, partially loaded, with variable structure, having a well-defined failure mechanism and assuming the addition of the third dimension in 2D models); probabilistic methods [55][56][57][58] (implies probabilistic analysis and processing of the physical-mechanical properties of the rocks and probabilistic computation by analytical or numerical methods); methods using Fuzzy logic [59][60][61][62][63] Considering the positive influence that lignite can exert on the stability reserve, due to its superior resistance characteristics compared to the surrounding (waste) rocks, Table 5 presents a situation regarding the position occupied by the lignite layers in relation to the slopes (existing, as of May 2023, and designed at the end of 2023). Next, in the model made with the help of the specialized software Slide (Figure 10), the values of the physical and mechanical characterist...…”
Section: Results Of the Stability Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, the literature has been enriched with numerous methods for stability analyses, developed by academics and researchers in the field, among which we mention: methods based on the limit equilibrium concept [1][2][3][4][5][7][8][9][10]; methods based on finite element/difference method [3,4,[7][8][9][10]12,13,49] (which is a modern and accurate one, able to be applied to complex structures); methods based on 3D analyses [29,40,41,[50][51][52][53][54] (for slopes with complex geometries, partially loaded, with variable structure, having a well-defined failure mechanism and assuming the addition of the third dimension in 2D models); probabilistic methods [55][56][57][58] (implies probabilistic analysis and processing of the physical-mechanical properties of the rocks and probabilistic computation by analytical or numerical methods); methods using Fuzzy logic [59][60][61][62][63] Considering the positive influence that lignite can exert on the stability reserve, due to its superior resistance characteristics compared to the surrounding (waste) rocks, Table 5 presents a situation regarding the position occupied by the lignite layers in relation to the slopes (existing, as of May 2023, and designed at the end of 2023). Next, in the model made with the help of the specialized software Slide (Figure 10), the values of the physical and mechanical characterist...…”
Section: Results Of the Stability Analysesmentioning
confidence: 99%
“…The main target of a stability study is to evaluate the safety factor (coefficient) or to verify the stability reserve of a slope and, on this basis, to mitigate the geotechnical risks that may occur by identifying and implementing the appropriate stabilization measures [3,5,13,14,41].…”
Section: Introductionmentioning
confidence: 99%
“…(1) In the reduction method considering the internal friction angle and cohesion of mesoscopic joints between blocks in the BBM-DFN model (CF-RM), failure of a highsteep scarp is mainly shown as shear failure along the joint planes in rock. Khan Muhammad Israr et al [42] suggested considering the trend of safety factor variation with changes in shear strength when analyzing slope stability. (2) The reduction method considering internal friction angle, cohesion, and tensile strength of mesoscopic joints between blocks in the BBM-DFN model (CFT-RM) holds that failure of rock in actual high-steep scarp engineering is compression-shear combined failure, so the tensile strength parameter of joints is incorporated into the reduction parameters.…”
Section: Strength Reduction Methods For Collapse Based On the Bbm-dfn...mentioning
confidence: 99%
“…In general, slope static stability analysis has matured, but due to the complexity of research on the mechanism of tensile cracks, stability analysis of slopes with cracks should be explored in much more detail systematically. A series of studies has shown that the failure surface of slope is a tensile-shear coupling failure surface, and the results of stability have also demonstrated the rationality of the analysis method [3][4][5][6][7][8]. However, in the process of slope stability analysis, for complex slip surface, how to determine the ultimate depth of tensile crack has become a prominent issue.…”
Section: Introductionmentioning
confidence: 99%